Evaluation of the Effects of Pesticide Residual Levels in Selected Grains - Mohammed-Kamil A. Piegu,; Fuseini J. Yakubu,; William Odoom,; Hayford Ofori, (International Journal of Scientific Research in Science and Technology, 2024)
The use of pesticides to protect stored products is on the ascendency in the grain industry in Ghana. Grains (maize, cowpea and groundnuts) were procured, stored for three months and levels of pesticides residue determined. It was revealed that pesticides levels were still high among all the grains after the storage period of three months. Pesticides residue obtained were potentially harmful to humans when the grains are consumed. Levels of pirimiphos-Methyl and permethrin in maize were 48.71 and 19.39 respectively. In cowpea, pirimiphos-Methyl and permethrin levels were respectively 46.46 and 13.53 and in groundnuts, levels of pirimiphos-Methyl and permethrin were 47.50 and 19.64 respectively. All the identified chemicals exceeded their maximum residual limits in grains.
Keywords: Maize; Cowpea; Groundnut; Residual Effect; Health Implications